Cyberbullying victimization predicts substance use and mental health problems in adolescents: data from a large-scale epidemiological investigation - Romualdo, Cláudio; de Oliveira, Wanderlei Abadio; Nucci, Luciana Bertoldi; Rodríguez Fernández, José Eugenio; da Silva, Laura Soares; Freires, Evelin Moreira; Vitta, Amanda Severo Lins; Semolini, Fernando Ferreira; Ferro, Lucas da Rosa; de Micheli, Denise; Andrade, André Luiz Monezi (Frontiers in Psychology, 2025)
PurposeThis study investigated the potential association of cyberbullying victimization (CyVic) on substance use and mental health-related behaviors among Brazilian adolescents, using data derived from the National Survey of School Health (PeNSE).MethodThe sample comprised 146,536 adolescents aged up to 17 years, who were selected through probabilistic and representative sampling. Participants were categorized into two groups: cyber-victim group (CYB), comprising those who reported experiencing threats, offense, or humiliation on social media platforms or messaging apps 30 days before the survey, and non-cybervictim group (nCYB).ResultsOf the participants, 13.3% were classified in the CYB group, with the majority being girls (61.9%) compared to boys (38.1%). The CYB group showed a significantly higher prevalence of substance use, with 22% of these youths reporting illicit drug use compared with 11% in the nCYB group. The CYB group also exhibited significant alcohol and tobacco consumption, as well as the initiation of these substances at a younger average age compared to the nCYB group. Sadness, helplessness, anxiety, and suicidal thoughts were significantly higher in the CYB group. The CYB group also reported lower parental understanding and a higher incidence of aggression, sexual abuse, and episodes of violence among peers and family members.ConclusionThe study results revealed the negative consequences of CyVic, emphasizing the need for effective strategies to address this issue and promote adolescent mental health.